Atomistic mechanisms of thermal transport across symmetric tilt grain boundaries in MgO. (1st June 2019) - Fujii, Susumu; Yokoi, Tatsuya; Yoshiya, Masato
Abstract: Grain boundaries often have a decisive effect on the macroscopic properties of polycrystalline materials, but the wide variety of their atomic structures, interfacial lengths, and compositions makes them difficult to characterize all-encompassingly. An indispensable example in which an understanding of the relationship between grain boundary structures and properties would greatly facilitate development of superior materials is thermal transport, especially with respect to microstructure evolution, thermoelectrics and thermal barrier coatings. To contribute to a more comprehensive understanding, we performed a systematic study of lattice thermal conduction across a wide range of symmetric tilt grain boundaries in MgO using perturbed molecular dynamics. It was found that thermal conductivities vary significantly with grain boundary structure but are strongly correlated with excess volume, which is a measure of the number density of atoms in the vicinity of the grain boundary planes. Real-space analysis revealed that dislocation densities determine the phonon transport paths and thermal conductivity in low-angle boundaries whereas it is the amount of open volume rather than the shape of structural units in high-angle boundaries that determine thermal conductivity. We also found that low-angle boundaries mainly reduce phonon transports at low frequencies whereas high-angle boundaries also reduce it at intermediate and high frequencies effectively, regardless of the shape of structural units. These insights are expected to be applicable to other close-packed oxide systems, and should aid the design of next-generation thermal materials through tailoring of grain boundaries. Graphical abstract: Image 1